Comparing physical, technical and tactical performances in the World Cup Qatar 2022 - Branquinho, L.; França, E.; Teixeira, J. E.; Valente, N.; Reis, T.; Thomatieli-Santos, R. V.; Forte, P.; Ferraz, R. (Journal of Human Sport & Exercise, 2024)
The main objective of this study was to compare the physical, technical, and tactical performances of the 32 teams that participated in the FIFA World Cup Qatar 2022™ concerning the confederation to which they belong and the FIFA ranking. Key statistics from the 64 matches played during the FIFA World Cup Qatar 2022™ were analysed. The data from these matches were encoded and calculated by a multi-camera optical tracking system (TRACAB Gen5, ChyronHego). Significant differences were identified between Rank 1-15th vs. Rank 16-35th and Rank 1-15th vs. Rank 36-61st for possession, total attempts at goal, total attempts on target, total passes, total complete passes, passes completion possession, completed line breaks, defensive line breaks, receptions in the final third, and ball progressions. However, defensive line breaks were different only between Rank 1-15th vs. Rank 36-61st, and ball progressions was only different between Rank 1-15th vs. Rank 16-35th. Africa and Europe national confederation showed significant differences (all p < .05) for possession, total attempts on target, total passes, total complete passes, passes completion, completed line breaks, and receptions in the final third, except for total attempts on target, whose differences are between Asian and South American confederation (p < .05). When considering the FIFA ranking and the confederations, there are significant differences key performance indicator of the teams.